2021
DOI: 10.3390/laws10030070
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation and Artificial Intelligence Applied to Business: Legal Regulations, Economic Impact and Perspective

Abstract: Digital transformation can be defined as the integration of new technologies into all areas of a company. This technological integration will ultimately imply a need to transform traditional business models. Similarly, artificial intelligence has been one of the most disruptive technologies of recent decades, with a high potential impact on business and people. Cognitive approaches that simulate both human behavior and thinking are leading to advanced analytical models that help companies to boost sales and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Digital Transformation and AI Applied to Business [16] The study discusses the legal regulations, economic impact, and perspective of digital transformation and AI applied to business. Limited exploration of the economic impact of AI in healthcare, manufacturing, and medical fields.…”
Section: Impact Of Ai and Digital Economy Onmentioning
confidence: 99%
“…Digital Transformation and AI Applied to Business [16] The study discusses the legal regulations, economic impact, and perspective of digital transformation and AI applied to business. Limited exploration of the economic impact of AI in healthcare, manufacturing, and medical fields.…”
Section: Impact Of Ai and Digital Economy Onmentioning
confidence: 99%
“…The outbreak and continuation of the coronavirus pandemic have further accelerated the digitalization process. Studies have shown that enterprises with a high degree of digital transformation tend to have better innovation capabilities [64], and high operational efficiency [65]. Their share price is relatively stable, and the risk of crash is lower [66].…”
Section: Digital Transformation State-owned Equity Participation and ...mentioning
confidence: 99%
“…From the beginning, we would like to point out that there has been a predilection in the scientific literature for the study of economic and other implications (including legal), present and future, of advances in the digital sphere and of artificial intelligence (Reier Forradellas and Gallastegui 2021a, 2021b, 2021c. The appreciable development of computer interconnectivity in all segments of society has led to an increasingly obvious trend of companies to use these networks in the area of a new type of commerce, e-commerce on the Internet, to appeal to new services in addition to the old ones (Mansell and When 1999).…”
Section: Literature Reviewmentioning
confidence: 99%